Chu fu : New year sacrifice - Yang, Bai; Heling, Wei; Lu, Xun, 1881-1936; Hu, Sang (China video movies., 1983)
Portrays the tragic life of Xianglan, a Chinese peasant woman, during the Chinese Revolution of 1911.